Functional mobility and flexibility in young female swimmers - Piekorz, Z.; Lewandowski, A.; Radziminska, A.; Weber-Rajek, M.; Siedlaczek, M.; Lulinska-Kuklik, E.; Moska, W. (Trends in Sport Sciences, 2017)
Swimming has become a very popular form of physical activity mainly due to its wholesome influence on the human body. The aim of this study was to determine the effects of swimming training on the functional mobility and flexibility of young female swimmers. It is believed that sw imming has a beneficial impact on the basic flexibility and functional mobility parameters. Material and Methods. Nine young female swimmers, members of the swimming team from 5th Secondary Sport School in Bydgoszcz took part in the study. The girls` functional mobility and flexibility in were determined twice the sagittal plane with the use of the FMS test and "Eurofit" test, respectively. The bend of the torso in the frontal plane was also assessed. The differences in results were measured with Student`s t-test, and the value of changes was determined using the Mollison index. Results. A slight increase in the final FMS test result was noted in the second examination, compared with the first one: from 16.88 ± 1.76 to 17.22 ± 2.28. In 25-35% of cases the risk of overloading muscles as well as the positive impact of training on flexibility levels in the sagittal and frontal planes (during a bend to the left) was detected: from 26.44 ± 9.73 to 29.66 ± 7.92, and from 23.33 ± 2.45 to 25.11 ± 3.18, respectively. The Mollison index revealed the most positive results in the rotational stability of the torso (1.65) and the range of the lateral bend to the left (0.73), while negative values were only found in the in-line lunge and chest mobility range (-0.42). Conclusions. The results of the study confirm that swimming training has a positive impact on the body of young swimmers (increased mobility and flexibility). It is of vital importance to undertake further research on the effects of swimming on the mobility of the human body.